THE FIRST GENERATION’S TACIT KNOWLEDGE TRANSFER - Saputra, Teddy (Jurnal Entrepreneur dan Entrepreneurship, 2018)
This study aims to see and learn when, how and what are the transfer of tacit knowledge between the senior generation and the next generation of first generation family companies in Surabaya. This is qualitative research. The study found that the transfer of tacit knowledge was planned and initiated by the senior generation. Transfers are carried out by observation, experiencing and reflection methods where unique senior generation knowledge such as trust in certain value values is transferred to the next generation which is then studied by the next generation to become a separate value.